Mental Health and Associated Factors among Software Professionals in Colombo - Sri Lanka - Kushaliny, P.; Kajavinthan, K. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
Mental health challenges among software professionals have gained attention, especially in high-pressure environments like Colombo, Sri Lanka. Long working hours, tight deadlines, and lack of support systems contribute to psychological distress, including stress, anxiety, depression, and burnout. This study aimed to explore the prevalence of mental health issues among software professionals in Colombo and identify demographic and work-related factors contributing to these challenges. A sample of 180 participants was surveyed using the General Health Questionnaire (GHQ-12) and semi-structured interviews, with a snowball sampling technique. The results showed that software professionals in Colombo experience higher levels of mental health issues than the general population, with a mean GHQ-12 score of 5.5944 (SD = 1.81766). Single professionals reported poorer mental health (mean = 5.7500) than married counterparts (mean = 4.8750). Age, work shifts, and working hours were significant factors, with older professionals reporting more distress. Work-related factors, such as heavy workloads and lack of recognition, were also linked to poorer mental health. The study found a concerning prevalence of maladaptive coping behaviours among those with higher mental distress. Participants with significant mental health challenges were more likely to engage in behaviours like alcohol consumption (4.15 times more likely), smoking (2.37 times more likely), sleep disturbances (7.60 times more likely), and overeating (3.95 times more likely). These findings highlight the need for better work-life balance, recognition, and mental health support to reduce burnout and improve the well-being of software professionals.
Keywords: Anxiety; Depression; Mental health; Software professional; Stress